PENYULUHAN PENTINGNYA PEMAHAMAN SISWA SMK PARIWISATA TENTANG SKILL YANG DIBUTUHKAN DALAM DUNIA KERJA PARIWISATA DI SMK DARMAWAN BOGOR - Djunaid, Ika Suryono (Jurnal Pengabdian dan Kewirausahaan, 2021)
ABSTRACT The tourism industry is defined as a collection of business fields that produce various services and goods needed by those who travel on a tour. Every product, whether real or virtual that is presented to meet specific human needs, should be assessed as an industrial product. As stated by the UNWTO (United Nations World Tourism Organization) in the International Recommendations for Tourism Statistics 2008, the tourism industry includes; accommodation for visitors, food and beverage service activities, passenger transportation, travel agencies and other reservation activities, cultural activities, and sports and entertainment activities.The skyrocketing world of tourism in Indonesia has an impact on other businesses, including hotels, restaurants and tourism management. The tourism industry is probably one of the most grueling industries to work in. For business people or Top Management companies in the tourism sector, the quality of human resources is a major factor that needs to be considered in order to be able to run the business optimally, this quality depends on the competence of human resources, namely a combination of Soft Skills and Hard Skills competencies.For this reason, it is imperative that vocational students must have a structure of knowledge and skills in order to enter the world of work and be able to adapt well after graduation and be able to access and use competencies optimally (competency dimensions).This Community Service activity was carried out on Tuesday, May 19, 2020 with the theme "Skills Needed in the World of Tourism Work at SMK Darmawan Bogor by using the online media Google Meet. The procedure for this service activity is carried out by providing attractive and easy-to-understand presentation material for students and students, the presentation of the material is prepared using power point media and several sample videos to facilitate the delivery stages to students and students. During the activity, based on the intensity of the questions and answers that arise, this Community Service activity provides benefits as additional motivation and increased knowledge for students in the future before entering the world of work in the tourism industry.